NOTE ON GEOGRAPHIC TOOLS FOR THE OBSERVATION OF CLIMATE CHANGE - López Martín, Fernando Germán; Martínez Cebolla, Rafael (Geographicalia, 2021)
The phenomenon of Climate Change has had in the last 25 years different ways of being represented and studied, most of them geographically. This article reflects on geographic tools for decision-making and the concrete example of the project on the Atlas of Climate Change of the Americas (ACCA) as a paradigm of collaboration between researchers and its contribution
Keywords: Climate change, Atlas, Geographical tools., Decision making